Hypothermia during sports swimming in water below 11 degrees C - Keatinge, W. R.; Khartchenko, M.; Lando, N.; Lioutov, V. (British Journal of Sports Medicine, 2001)
OBJECTIVES:To assess precautions needed to avoid dangerous hypothermia in endurance sports swims in water below 11 degrees C, using rectal temperature, anthropometric measurements, and voluntary swim times during a six day marathon relay swim. METHODS:The time in the water and the decrease in rectal temperature were measured during the longest of three to five relay swims by each of eight experienced swimmers in 9.4-11.0 degrees C water. Height, weight, and four skinfold thicknesses were measured. RESULTS:Swimmers with less subcutaneous fat terminated their swims after significantly less time in the water than those with thicker skinfold thickness, even though their rectal temperatures were not significantly lower. The lowest rectal temperature recorded was 34.3 degrees C. CONCLUSIONS:Subjective sensation in these experienced swimmers gave reliable guidance on safe durations for swims, and all voluntarily left the water with rectal temperatures that present no threat to people able to rewarm in safe surroundings. Endurance swims in highly competitive conditions or water below 9 degrees C may require continuous temperature monitoring for safety.